(3aUhd bUGQ ef GdcdGe GdHdjZs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3MQa GdCda EjeGf GdeQA jYQa HCjeGfg s
(3BNQgG (B:s
(3ef MQa GdjGA (B: (3jfcSa fhQ GdOjf EPG Yde ef dG hQY dg s
(3HgG fXGe GdJYbjHIs
(3eQJHI Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(328 / 4(3b(B) s
Keywords: (3GdCOHs